Microbiome Research in Greece: A Comprehensive Bibliometric Study - Christos Stefanis; Christina Tsigalou; Ioanna Bezirtzoglou; Chrysoula (Chrysa) Voidarou; Elisavet Stavropoulou (Microorganisms)
Bibliometric analyses are increasingly used to evaluate scientific domains, revealing research trends, productivity, and impact. This study provides a bibliometric analysis of microbiome-related research conducted by Greek scientists. Data were retrieved from the Scopus database, using the keyword “microbiome” (English) for publications until December 2024. Bibliometric analysis was performed using VOSviewer and the bibliometrix package in R. Our findings indicate that research output has increased exponentially since 2018, with the National and Kapodistrian University of Athens and the Aristotle University of Thessaloniki leading microbiome research in Greece. Medicine, biochemistry, genetics, molecular biology, immunology, and microbiology are the predominant research fields. The keyword analysis highlights “microbiome”, “microbiota”, “probiotics”, “prebiotics”, “intestinal flora”, and “16S rRNA” as central topics. Additionally, we acknowledge the role played by alternative microbial markers, including 18S rRNA/ITS sequencing, for fungal diversity studies. This bibliometric study demonstrates a dynamic and evolving research landscape in Greece and highlights the international relevance of Greek contributions to microbiome science.